Early detection of developmental delay in infants born very preterm or with very low birthweight. (17th September 2022) - Caesar, Rebecca A.; Boyd, Roslyn N.; Cioni, Giovanni; Ware, Robert S.; Doherty, Julie; Jackson, Maxine P.; Salthouse, Kaye L.; Colditz, Paul B.; ,
Abstract: Aim: This study aimed to identify early clinical biomarkers from birth to 16 weeks corrected age to predict typical outcome and developmental delay in infants born very preterm or with very low birthweight. Method: A prospective cohort of infants on the Sunshine Coast, Australia, was assessed using the Premie‐Neuro Examination, the General Movement Assessment (GMA), the Alberta Infant Motor Scale, and the Infant Sensory Profile 2. At 24 months corrected age, delay was identified using the Bayley Scales of Infant and Toddler Development, Third Edition (Bayley‐III) and Neurosensory Motor Developmental Assessment (NSMDA). Results: One hundred and four infants were recruited; 79 completed outcome assessments (43 females, 36 males; mean gestational age 30 weeks [SD 1 week 6 days], mean birthweight 1346 g [SD 323]). The incidence of developmental delay (motor or cognitive) was 6.3%. Suboptimal quality of fidgety general movements (temporal organization) at 16 weeks corrected age demonstrated the best predictive accuracy (Bayley‐III motor: sensitivity 100% [95% confidence interval CI 3–100], specificity 75% [95% CI 63–84], area under the curve [AUC] 0.87); Bayley‐III cognitive: sensitivity 100% [95% CI 3–100], specificity 75% [95% CI 64–84], AUC 0.88); NSMDA motor: sensitivity 100% [95% CI 40–100], specificity 81% [95% CI 70–90], AUC 0.91 [95% CI 0.86–0.95]). GMA trajectories that combined abnormal writhing general movements at 4 to 5 weeks corrected age with suboptimal quality of fidgety movement at 16 weeks corrected age were strongly predictive of developmental delay, superior to all other clinical tools, and perinatal and demographic variables investigated ( p = 0.01, Akaike information criterion method 18.79 [score corrected for small sample size], accounting for 93% of the cumulative weight). Interpretation: Only the GMA had sufficient predictive validity to act as a biomarker for both conditions: typical outcome and developmental delay (motor or cognitive). GMA trajectories that assessed both writhing general movements at 4 to 5 weeks corrected age and quality of fidgety movement at 16 weeks corrected age predicted adverse neurodevelopmental outcome, accurately differentiating between infants with typical outcomes and those at increased risk for motor or cognitive delay. Abstract :